Biostratigraphy of the Aptian-Albian calcareous nannofossils of the Essaouira-Agadir Basin (NW Africa) - Ahmed Awad Abdelhady; Walid Kassab (PANGAEA, 2017)
Aptian-Albian calcareous nannofossil record of the Essaouira-Agadir Basin.